Breath Ketone Testing: A New Biomarker for Diagnosis and Therapeutic Monitoring of Diabetic Ketosis. (11th May 2014) - Qiao, Yue; Gao, Zhaohua; Liu, Yong; Cheng, Yan; Yu, Mengxiao; Zhao, Lingling; Duan, Yixiang; Liu, Yu
Abstract : Background . Acetone, β -hydroxybutyric acid, and acetoacetic acid are three types of ketone body that may be found in the breath, blood, and urine. Detecting altered concentrations of ketones in the breath, blood, and urine is crucial for the diagnosis and treatment of diabetic ketosis. The aim of this study was to evaluate the advantages of different detection methods for ketones, and to establish whether detection of the concentration of ketones in the breath is an effective and practical technique. Methods . We measured the concentrations of acetone in the breath using gas chromatography-mass spectrometry and β -hydroxybutyrate in fingertip blood collected from 99 patients with diabetes assigned to groups 1 (−), 2 (±), 3 (+), 4 (++), or 5 (+++) according to urinary ketone concentrations. Results . There were strong relationships between fasting blood glucose, age, and diabetic ketosis. Exhaled acetone concentration significantly correlated with concentrations of fasting blood glucose, ketones in the blood and urine, LDL-C, creatinine, and blood urea nitrogen. Conclusions . Breath testing for ketones has a high sensitivity and specificity and appears to be a noninvasive, convenient, and repeatable method for the diagnosis and therapeutic monitoring of diabetic ketosis.